Ruptured Suprasellar Dermoid Cyst presenting with Chemical Meningitis and Blindness - Lakshya Varshney; Laxminarayan Tripathy; Harsh Jain; Sunandan Basu; Mohammad Sarwar (National Board of Examinations Journal of Medical Sciences)
Background: Intracranial dermoid cysts (ICDC) are rare benign lesions. They typically originate from the ectoderm and contain dermal elements like hair follicles, sweat glands, sebaceous glands, and sometimes teeth. Ruptured suprasellar dermoid cysts with intracranial dissemination are extremely rare. Case presentation: We report one such patient who presented with headache and blindness, imaging suggestive of ruptured intracranial dermoid cyst. We performed a pterional craniotomy and excised the tumor and the diagnosis was consistent with dermoid cyst on histopathology. Conclusion: Rare cases should be reported for further scientific advancements and a better understanding of physicians in the future if they encounter.